The effects of 8-week aerobic training on body weight among sedentary females - Gamze Ozdil; Ozlem Bagıs; Faruk Guven; Samet Aktas (Türk Spor ve Egzersiz Dergisi)
In this study, it was intended to see how a-8 week aerobic traininig applications affected weight loss and body composition among the sedentary females. A training programme of aerobic training (walking and cycling) with mild abdominal, arm and hip exercises was carried out for 60 minutes in 3 days of a week (Monday, Wednesday and Friday) during 8 weeks. Age, height and weight values regarding ones participated in the study were given as mean and standart deviation. Paired-Sample T test was used to compare pre and post test values of the group participated in the study. The statistical significance level was regarded as 0.05. The participants had age average of 23.27 ± 5.04, body weight average of 62.99 ± 9.49, height average of 163.00 ± 3.95. Statistically significant differences were not observed in weight, arm, shoulder, breast, leg and hip values concerning the participiants (p lt;0.05). Differences were observed in the pre and post test values. There was not statistically significant differences when comparing the pre and post tests of the waist measurements. As a result; a 8-week aerobic training application affected positively weight loss and body composition among the sedentary females.